ACCOUNTING REQUIREMENTS FOR FOREIGN INVESTORS IN PARAGUAY - Carlos Lezme Maldonado, Juan; Elida Peralta Llanes, María; Paola Ramírez Oviedo, Liz (Revista Gênero e Interdisciplinaridade, 2023)
The research work aims to expose the necessary requirements to make an investment in Paraguay, the determinants that motivate foreign firms to invest and operate. In this context, first a brief theoretical description is made to then give way to a descriptive analysis, resulting in a lack of important knowledge on the part of professionals about what a foreign investor needs to start their company.